Effect of tooth background color on the visual color adjustment potential of single-shade resin composites - Kanchanomai, Virada; Saikaew, Pipop; Harnirattisai, Choltacha; Chaichalothorn, Munin (Mahidol Dental Journal, 2025)
Objectives: This study aimed to assess the impact of different background tooth colors on the visual color adjustment potential (CAP- V) of two single-shade flowable resin composites, evaluating their suitability for anterior restorations. Materials and Methods: Two single-shade flowable composite resins (Omnichroma : OMN and Essentia Highflo : ESH) were evaluated. Two different shades (A1 and A3.5) of Shofu Disk HC were milled into maxillary right central incisor models with a 1 mm MID bevel preparation to serve as background colors. Dual specimens (artificial central incisor models restored with the tested composites) and single specimens (Composite central incisor models) of all test materials were prepared (n = 5 per group). Visual scoring of color matching was performed by independent observers under controlled conditions. CAP-V values were calculated based on the visual scores. Statistical analysis was performed using Two-way analysis of variance (ANOVA) with a significance level set at α = 0.05. Results: CAP-V values and visual scores were significantly influenced by the composite resin type, tooth shade, and their interaction (p< 0.001). Positive CAP-V values were observed for all tested materials. Among them, OMN demonstrated a significantly higher CAP-V in the A1 shade compared to ESH, which corresponded with a lower visual color score. In the A3.5 shade, OMN and ESH exhibited similar CAP-V values; however, ESH showed a significantly lower visual color score. Conclusions: OMN could serve as an alternative material for the injection molding technique in anterior teeth with lighter shades, while ESH may be more suitable for darker shades.